2005
DOI: 10.1126/science.1117569
|View full text |Cite
|
Sign up to set email alerts
|

Voyager 1 in the Foreshock, Termination Shock, and Heliosheath

Abstract: Voyager 1 (V1) began measuring precursor energetic ions and electrons from the heliospheric termination shock (TS) in July 2002. During the ensuing 2.5 years, average particle intensities rose as V1 penetrated deeper into the energetic particle foreshock of the TS. Throughout 2004, V1 observed even larger, fluctuating intensities of ions from 40 kiloelectron volts (keV) to >/=50 megaelectron volts per nucleon and of electrons from >26 keV to >/=350 keV. On day 350 of 2004 (2004/350), V1 observed an intensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
303
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(328 citation statements)
references
References 16 publications
(10 reference statements)
17
303
0
1
Order By: Relevance
“…The bulk speed V in the heliosheath [Richardson and Wang, 2010], observed by the plasma instrument on V2 [Bridge et al, 1977], has been twice as high as that observed by Voyager 1 (V1) when it crossed TS in December, 2004 [Stone et al, 2005;Gurnett and Kurth, 2005;Decker et al, 2005;Burlaga et al, 2005a]. These high speeds were observed from the last crossing of the TS in September 1, 2007September 1, (2007 to 2009.7.…”
Section: Introductionmentioning
confidence: 65%
“…The bulk speed V in the heliosheath [Richardson and Wang, 2010], observed by the plasma instrument on V2 [Bridge et al, 1977], has been twice as high as that observed by Voyager 1 (V1) when it crossed TS in December, 2004 [Stone et al, 2005;Gurnett and Kurth, 2005;Decker et al, 2005;Burlaga et al, 2005a]. These high speeds were observed from the last crossing of the TS in September 1, 2007September 1, (2007 to 2009.7.…”
Section: Introductionmentioning
confidence: 65%
“…Christon 1987;Collier and Hamilton 1995;Grabbe 2000;Mauk et al 2004;Schippers et al 2008;Dialynas et al 2009;Ogasawara et al 2013), outer heliosphere and inner heliosheath (e.g. Decker and Krimigis 2003;Decker et al 2005;Heerikhuisen et al 2008;Zank et al 2010;Livadiotis et al 2011Livadiotis et al , 2013, and other general plasma analyses (e.g. Milovanov …”
Section: Introductionmentioning
confidence: 99%
“…Also using WIND data, Chotoo et al [2000] analyzed power law tails associated with corotating interaction regions and extracted the values of k. The 2004 Voyager 1 termination shock crossing extends suprathermal tail observations into the heliosheath. The Voyager 1 LECP instrument observed a k = 1.6 power law tail for hydrogen ions at v ) v sw [Decker et al, 2005]. While the acceleration mechanism for the power law tail is under debate, the diversity of regimes in which it has been observed indicates that it is a universal characteristic of plasma throughout the heliosphere and heliosheath.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, the Voyager 1 and 2 Low Energy Charged Particle (LECP) detectors have established that a power law describes the heliosheath ions downstream of the termination shock in the energy range of $30 keV to 10 MeV [Decker et al, 2005; R. B. Decker et al, Voyager 2 encounter with an energetic-particle-mediated termination shock, submitted to Science, 2008]. Below 30 keV there is an unmeasured energy region, including the $0.01 -6 keV that will be investigated by IBEX.…”
Section: Introductionmentioning
confidence: 99%